231k views
2 votes
HELP WHICH EXPRESSION

HELP WHICH EXPRESSION-example-1

2 Answers

3 votes

Answer:


(n^(-3)) ^(6)

Step-by-step explanation:

Using the rules of exponents


(a^(m)) ^(n)
a^(mn)


a^(-m)
(1)/(a^(m) )

Consider


(n^(-3)) ^(6)

=
n^(-3(6))

=
n^(-18)

=
(1)/(n^(18) )

The other 3 all simplify to
n^(18)

User KBriggs
by
5.3k points
3 votes
Answer:
(n^-3)^6

Step-by-step explanation:
(n^-3)^6
=n^-18

We can use the law that a^-n=1/a^n to help us simplify n^-18.

n^-18
=1/n^18

I hope this helps! Please comment if you have any questions.
User Zotherstupidguy
by
4.9k points